Immunological characterization of a gammadelta T-cell stimulatory ligand on autologous monocytes - Sathiyaseelan, Thillainayagam; Naiman, Brian; Welte, Stefan; MacHugh, Niall D.; Black, Samuel J.; Baldwin, Cynthia L. (Wiley, 2002)
Bovine γδ T cells are stimulated to proliferate by autologous monocytes. This is referred to as the autologous mixed leucocyte reaction (AMLR). It has been shown previously that the stimulatory component is constitutively expressed on the monocyte plasma membrane and is a protein or has a protein moiety. Here we showed that γδ T‐cell responses to the monocytes requires interaction with the T‐cell receptor because Fab1 fragments of a monoclonal antibody (mAb) that reacts with the δ chain of the T‐cell receptor blocked proliferation in the AMLR. Monocyte molecules involved in stimulation were also characterized further by biochemical and immunological methods. A mAb, named M5, was generated by immunizing mice with bovine monocytes and shown to block the ability of monocytes to stimulate in the AMLR. Treatment of monocytes or monocyte membranes with high salt, chelating agents or phospholipase C did not affect their ability to stimulate γδ T‐cell proliferation or reactivity with mAb M5 indicating the ability of monocytes to stimulate does not involve peripheral membrane components or a glycosyl‐phosphatidylinsositol (GPI)‐anchored components. Hence it was concluded that the stimulation occurred as a result of intergral membrane proteins including that recognized by mAb M5. The ligand for mAb M5 was on all bovine monocytes and to a lower level on granulocytes but not on lymphocytes. MAb M5 also reacted with sheep monocytes but not with human monocytes or murine macrophages, in agreement with a previous reports that sheep monocytes but not human or mouse mononuclear phagocytes have the capacity to stimulate bovine γδ T cells in in vitro cultures. The level of expression of the M5 ligand was not altered by γ‐irradiation or culture of monocytes with lipopolysaccharide but it was decreased following culture with interferon‐γ‐containing cell culture supernatants.